Observations of strong ground motion at hill sites in Mexico City from recent earthquakes - F. J. Sánchez-Sesma; E. Reinoso-Angulo; J. C. Montalvo-Arrieta (Geofísica Internacional, 2003)
Results of seismic response of the stations of the Acelerometric Network of Mexico City located in the hill zone are presented. Seven earthquakes from different seismic sources were analyzed, with magnitudes between 5.9 and 7.3. There is a dependence of the seismic response at hill sites on earthquake magnitude, azimuth, epicentral distance and depth. Subduction earthquakes concentrate their energy at low frequencies (<1 Hz), while intraplate earthquakes have frequencies higher than 1 Hz. We find two significant types of amplification: regional, for sites located to the southwest hill zone over sites located to the north of the city, and local. Stations located in the southwest area show higher amplification with respect to the reference station. The spectral ratios of stations located in the central and southwest part of the hill zone show relative amplifications up to four times higher than stations located in the north area of the city for frequencies between 1 and 3 Hz. These local amplifications may be due to the presence of soft material under the lava flows where the stations are located.